Unveiling a New Species of Fanged Frog (Amphibia: Anura: Dicroglossidae) from Southeastern Borneo, Indonesia - Ade Damara Gonggoli; Tomohiko Shimada; Kanto Nishikawa; Masafumi Matsui; Thornton Larson; Eric N. Smith; Amir Hamidy (Species Diversity)
We describe a new species of anuran in the species complex of Limnonectes kuhlii (Tschudi, 1838) from the Meratus Mountain Range of Borneo Island, Indonesia. Mitochondrial DNA analysis places the new species as a sister of L. cintalubang Matsui, Nishikawa, and Eto, 2014. The new taxon differs from all other recognized species of L. kuhlii complex by a large genetic distance and a combination of morphological, bioacoustic, and larval characteristics. This discovery provides new insights into the taxonomic diversity of the L. kuhlii complex in Borneo, particularly within the Meratus Mountain Range, and highlights the importance of conserving this unique and understudied region.